Genetic Diversity of Recent Infectious Bursal Disease Viruses Isolated From Vaccinated Poultry Flocks in Malaysia - Aliyu, Hayatuddeen Bako; Hair-Bejo, Mohd; Omar, Abdul Rahman; Ideris, Aini (Frontiers in Veterinary Science, 2021)
Vaccination is an essential component in controlling infectious bursal disease (IBD). However, there is a lack of information on the genetic characteristics of recent infectious bursal disease virus (IBDV) isolated from IBD vaccinated commercial flocks in Malaysia. The present study investigated 11 IBDV isolates isolated from commercial poultry farms. The isolates were detected using reverse transcription-polymerase chain reaction (RT-PCR) targeting the hypervariable region (HVR) of VP2. Based on the HVR sequences, five isolates (IBS536/2017, IBS624/2017, UPM766/2018, UPM1056/2018 and UPM1432/2019) were selected for whole-genome sequencing using the MiSeq platform. The nucleotide and amino acid (aa) sequences were compared with the previously characterised IBDV strains. Deduced aa sequences of VP2HVR revealed seven isolates with 94 - 99% aa identity to very virulent strains (genogroup 3), two isolates having 97 - 100% aa identity to variant strains (genogroup 2), and two strains with 100% identity to vaccine strain (genogroup 1) of IBDV. Also, the phylogenetic analysis showed that the isolates formed clusters with the respective genogroups. The characteristic motifs: 222T, 249K, 286I, and 318D typical of the variant strain were observed for UPM1219/2019 and UPM1432/2019. In comparison, very virulent residues; 222A, 249Q, 286T, and 318G were found for the vvIBDV except for UPM1056/2018 strain with A222T substitution. In addition, the isolate has aa substitutions such as D213N, G254D, S315T, S317R and A321E that are not commonly found in previously reported vvIBDV strains. Unlike the other vvIBDV characterised in this study, UPM766/2018 lacks the MLSL aa residues in VP5. The aa tripeptides: 145/146/147 (TDN) of VP1 were conserved for the vvIBDV, while a different motif, NED was observed for the Malaysian variant strain. The phylogenetic tree showed that the variant IBDV clustered with the American and Chinese variant viruses and highly comparable to the Chinese novel variants with 99.9% identity. Based on the sequences and phylogenetic analyses, the first identification of a variant IBDV in Malaysia is reported. Further research is required to determine the pathogenicity of the variant IBDV and the protective efficacy of the currently used IBD vaccines against the virus.